Research on a Miniature Underwater Vehicle Based on a Multi-Unit Underwater Coupled Jet Drive - Dong Zhang; Xingming Ma; Xue Zhang; Peng Gao; Kai Li (Actuators)
The underwater unstructured environment poses new challenges for the miniaturization and flexibility of underwater vehicles. This paper proposes a method of using micrometer-scale vibrations of piezoelectric vibrators to drive macroscopic jets. Then, we use two coupled piezoelectric jet driving units to construct a miniature underwater vehicle. Numerical simulation is used to investigate the flow field characteristics of coupled jets. Finally, the impact of the angle between the two piezoelectric jet drive units on the propulsion force is analyzed. The miniature underwater vehicle measures 77.8 mm in length and 87 mm in width. While achieving miniaturization, it maintains high flexibility, maneuverability, and controllability. By adjusting the input signals to the two piezoelectric jet drive units, the miniature underwater vehicle can move in a straight line, turn, and rotate. Its maximum linear velocity reaches 54.23 mm/s. Its outstanding motion ability and environmental adaptability allow it to perform various tasks in unknown and complex environments. It also has broad application prospects.